Family history of disease and risk of glioma occurrence: Results of the case-control study - Azanjac-Arsić Ana; Tončev Gordana; Miletić-Drakulić Svetlana; Vesić Katarina; Aleksić Dejan; Marić Gorica; Pekmezović Tatjana (Vojnosanitetski Pregled, 2020)
Background/Aim. Malignant gliomas represent a heterogenaus group of tumors. They occur in all age groups, predominatly in males in older age. The purpose of this case-control study was to examine the association between risk for developing glioma and family history of diseases. Methods. The case-control study included 100 pathologically confirmed cases of glioma at the Clinical Centre Kragujevac, Serbia, between 2015 and 2016, and 200 ageand sex-matched controls without glioma and other malignant diseases in personal and family history at the same institution. After signing the informed consent all the patients filled out an epidemiological questionnaire. Multivariate logistic regression analysies was used in statistical data processing. Results. Malignant diseases in family history were more common in the study group than in the control group [odds ratio (OR) = 1.821, 95% confidence interval (CI) 1.004–3.305; p = 0.049]. The most common malignant tumor in the study group were cancer of the uterus (7%) and colon cancer (6%), while in the control group the most common cancer were lung cancer (6%) and cancer of the uterus (7%). Diabetes mellitus in family history was more common among control individuals than among glioma patients (OR = 0.520, 95% CI = 0.271– 0.995; p = 0.048). Also, our results showed that cardiovascular diseases in family history were more common in the control group than among patients of the study group (OR = 0.557, 95% CI = 0.325–0.953; p = 0.033). Conclusion. In this case-control study, we observed a statistically significant relation between family history of malignant diseases and glioma. Also, we found statistically significant inverse relation between family history of cardiovascular diseases and diabetes and glioma.